2013
DOI: 10.1107/s0907444913009335
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of X-ray damage in macromolecular crystallography by submicrometre line focusing

Abstract: Reported here are measurements of the penetration depth and spatial distribution of photoelectron (PE) damage excited by 18.6 keV X-ray photons in a lysozyme crystal with a vertical submicrometre line-focus beam of 0.7 µm full-width half-maximum (FWHM). The experimental results determined that the penetration depth of PEs is 5 ± 0.5 µm with a monotonically decreasing spatial distribution shape, resulting in mitigation of diffraction signal damage. This does not agree with previous theoretical predication that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The previous observation by Sanishvili et al indicated the presence of perturbations extending a few micrometers beyond the X-ray-exposed regions (12), consistent with the proposed redistribution of charge and the production of strong local electric fields (14,15). The experimentally measured parameters describing the mean propagation distance of the photoelectrons based on the SHG images are in remarkably good quantitative agreement with the Monte Carlo simulations.…”
Section: Resultssupporting
confidence: 76%
“…The previous observation by Sanishvili et al indicated the presence of perturbations extending a few micrometers beyond the X-ray-exposed regions (12), consistent with the proposed redistribution of charge and the production of strong local electric fields (14,15). The experimentally measured parameters describing the mean propagation distance of the photoelectrons based on the SHG images are in remarkably good quantitative agreement with the Monte Carlo simulations.…”
Section: Resultssupporting
confidence: 76%
“…Our findings suggest that in some cases the lack of inclusion of PE escape leads to deviations from the behaviour predicted by RADDOSE-3D [9] (see, for example, [14,16,17]). This conclusion is supported by both the similarity in output to RADDOSE-3D under conditions where PE escape is unlikely to affect dose (or when it has been ignored in our models), and the divergence in output under conditions where PE escape is expected to be significant.…”
Section: Prediction Of Extended Lifetimes For Small Crystals and Beammentioning
confidence: 77%
“…The similarity in values of f NH indicate that our simulation results are comparable to the Holton and Frankel model. In addition to qualitative comparisons to previous modelling studies, a semi-quantitative assessment of our model can be conducted by comparison to recent results obtained by Finfrock et al [16,18] and Sanishvili et al [17], who performed experimental studies of radiation damage in large crystals by exposing sub-volumes using micro-focus and line-focus beams. They observed that the radiation damage footprint extended between 1.5 µm and 5 µm beyond the actual beam footprint, showing the spread of PEs beyond the diffraction volume.…”
Section: Simulations Enabling Qualitative and Semi-quantitative Intermentioning
confidence: 99%
See 2 more Smart Citations